Racial Bias in National Football League Officiating - Eiserloh, Dawson G.; Foreman, Jeremy J.; Heintz, Elizabeth C. (Frontiers in Sociology, 2020)
Racial bias in sport is a prevalent research topic. Much of the previous research regarding bias among referees in sport focused on sports such as baseball, basketball, hockey, and soccer. Professional American football is unique because race is more clearly defined when compared to these other sports. Additionally, by examining holding penalties, which are known to be more subjective and called predominately by a single official on the field (i.e., the umpire), racial bias in officiating can be more efficiently analyzed in professional American football. The purpose of this study is to examine potential racial bias regarding holding penalties in the National Football League (NFL). Three years of data from the 2013 to 2014 through 2015 to 2016 NFL seasons were used, including the races of officials and players involved in holding penalties. Results showed no evidence of racial bias in the calling of holding penalties by White officials. However, Black umpires were found to call more holding penalties when led by a White referee. Additionally, Black players were more likely to have holding penalties called on them earlier in the game by all officials.